Examining the structural pathways linking learning motivation, mathematical problem-solving, and critical thinking in junior high school mathematics - Lukman, Hamidah Suryani; Sholihat, M Nuur'aini; Jupri, Al; Kusnandi (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to examine the structural relationships among learning motivation, mathematical problem-solving ability, and students’ mathematical critical thinking, with mathematical problem-solving ability modeled as a mediating construct. Method: The study employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) involving three main constructs: learning motivation, mathematical problem-solving ability, and mathematical critical thinking skills. Data were collected through performance-based essay tests measuring students’ mathematical problem-solving and critical thinking skills, complemented by a 5-point Likert-scale questionnaire to assess learning motivation, involving 124 junior high school students from three schools in Sukabumi City, Indonesia. The data were analyzed using Smart-PLS 4. Findings: The results indicate that learning motivation has a significant effect on mathematical problem-solving ability, while problem-solving ability has a strong influence on students’ mathematical critical thinking skills. The direct effect of motivation on critical thinking is significant but smaller than its indirect effect through problem-solving ability. Mediation analysis confirms that problem-solving ability functions as a partial mediator. In addition, The PLS-predict analysis revealed that most indicators exhibited Q² predict values greater than zero and lower prediction errors than the linear model benchmark, indicating that the proposed model demonstrates acceptable out-of-sample predictive power. Significance: Beyond prior motivation–critical thinking studies, this research clarifies the structural pathway through which learning motivation is associated with mathematical critical thinking by positioning mathematical problem-solving ability as a partial mediator in junior high school mathematics learning.